2021
DOI: 10.3390/diagnostics11050743
|View full text |Cite
|
Sign up to set email alerts
|

Omics and Artificial Intelligence to Improve In Vitro Fertilization (IVF) Success: A Proposed Protocol

Abstract: The prediction of in vitro fertilization (IVF) outcome is an imperative achievement in assisted reproduction, substantially aiding infertile couples, health systems and communities. To date, the assessment of infertile couples depends on medical/reproductive history, biochemical indications and investigations of the reproductive tract, along with data obtained from previous IVF cycles, if any. Our project aims to develop a novel tool, integrating omics and artificial intelligence, to propose optimal treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Markedly, artificial neural networks (ANNs), and in general artificial intelligence (AI) methods, historically seem to have a good fit in the metabolomics arena [ 50 ]; nowadays, deep learning, being the forefront of ANNs and AI research, was already employed in metabolomics’ applications [ 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Markedly, artificial neural networks (ANNs), and in general artificial intelligence (AI) methods, historically seem to have a good fit in the metabolomics arena [ 50 ]; nowadays, deep learning, being the forefront of ANNs and AI research, was already employed in metabolomics’ applications [ 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…A step towards that direction could be a panel—preferably international—in which all biomarkers that are discovered by NMR and that concern specific infertile populations with different phenotypes or etiologies, such as those with repeated implantation failures or poor/high response to ovarian stimulation, are stored. A recent study protocol proposed how the measurement of different classes of metabolomics parameters may be incorporated into such a large database of patient demographics, previous cycle characteristics, used protocols, underlying infertility conditions, sperm as well as other “omics” parameters and, with the assistance of ANNs, provide valuable predictions of IVF outcomes (i.e., clinical pregnancy rates, live birth rates, miscarriage rates, multiple pregnancy rates) [ 53 ]. Even without the implementation of AI, such a database would be extremely meaningful as it would be able to address one of the main pitfalls of metabolomics’ utilization in IVF so far; that is, the inconsistency between different studies, patients, and settings [ 9 ], or even the variability between metabolomics biomarkers used [ 10 , 11 , 19 , 21 , 33 ].…”
Section: Suggested Stepsmentioning
confidence: 99%
“…Furthermore, in a recent paper from the authors' team of the current study, "omics" combined with predictive models have been suggested to have the ability to substantially promote health management individualization and contribute to the successful treatment of infertile couples, particularly those with unexplained infertility or repeated implantation failures and, in rare cases, those currently reported in this review [47].…”
Section: The Main Recommendation: Genetic Analysis and Bioinformaticsmentioning
confidence: 99%
“…There are also new fields in biological data, such as exomics, lipidomics, and secretomics. "Omics" data are a valuable parameter for embryo selection optimization and promoting personalized IVF treatment [47]. For example, proteomics is an emerging, powerful diagnostic tool, with applications ranging from biomarker identification for effective embryo and oocyte selection and high-risk pregnancy management, to tissue engineering guidance [48].…”
Section: The Main Recommendation: Genetic Analysis and Bioinformaticsmentioning
confidence: 99%
See 1 more Smart Citation